Implementation of filters for image pre-processing for leaf analyses in plantations - Mertes, Jacqueline Gomes [UNESP]; Marranghello, Norian [UNESP]; Pereira, Aledir Silveira [UNESP] (Springer Nature, 2008)
In this work an image pre-processing module has been developed to extract quantitative information from plantation images with various degrees of infestation. Four filters comprise this module: the first one acts on smoothness of the image, the second one removes image background enhancing plants leaves, the third filter removes isolated dots not removed by the previous filter, and the fourth one is used to highlight leaves' edges. At first the filters were tested with MATLAB, for a quick visual feedback of the filters' behavior. Then the filters were implemented in the C programming language. At last, the module as been coded in VHDL for the implementation on a Stratix II family FPGA. Tests were run and the results are shown in this paper. © 2008 Springer-Verlag Berlin Heidelberg.
Keywords: Digital image processing; Hardware description language application; Precision agriculture; Reconfigurable architectures; BASIC (programming language); C (programming language); Computer programming languages; Computer software; MATLAB; Visual communication; C programming languages; Computational sciences; Heidelberg (CO); Image pre-processing; International conferences; Quantitative information; Visual feedback; Wave filters